PENDIDIKAN BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI - Asmawi Asmawi; Syafei Syafei; Muhammad Yamin (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
In the present time, the development of information technology, especially in Indonesia, is growing. With the existence of information and communication technology can make it easier for us to learn and get information that we need from anywhere, anytime, and from anyone. In the education world, the development of information technology has begun to have a positive impact because the development of information technology in the education world has begun to show significant changes. Nowadays distance and time are not significant problems to gain knowledge, various applications are created to facilitate them. Information technology is a technology used to process data, including processing, obtaining, compiling, storing, manipulating data in various ways to produce quality information that is relevant, accurate, and timely information, which is used for personal, business, and government and is strategic information for decision making.